Interfacial regulation induced rate capability and cycling stability of poly(perylene diimide) organic electrode - Xijie Fu; Xinxin Liu; Yue Sun; Xiangming Feng; Cuiping Li; Zi-Feng Ma; Jinyun Zheng; Weihua Chen (Materials Reports: Energy)
Organic electrodes are considered competitive candidates for the next-generation high-performance energy storage devices owing to their advantages of structural flexibility and abundant resources. However, solubility and low electronic conductivity have been major obstacles to the practical application. To address these challenges, the structural design and interfacial regulation of organic electrodes are crucial to the performance enhancement. Herein, we report on a π-conjugated polymer cathode material of poly(3,4,9,10-perylenetetracarboxylic diimide) (PPI) for metal ion batteries, and the performance optimization is achieved by matching suitable conductive carbons and liquid electrolytes. Ultimately, the carbon nanotubes (CNTs) with weight content of 25% and 1 M NaPF6 in ethylene carbonate/diethyl carbonate electrolyte are introduced to assemble the batteries, and the discharge specific capacity, cycling stability and rate performance are enhanced effectively. The PPI-CNT||Na battery displays high specific capacities of 146.4 and 117 mAh g−1 at current densities of 0.1 C and 5 C, respectively. Furthermore, PPI-CNT||Na battery demonstrates excellent long-term cycling stability of 5000 cycles with low 0.007 mAh g−1 capacity decay per cycle at 1C due to the thin and uniform cathode electrolyte interphase. Moreover, the PPI-CNT||Na battery presents good cycling stability at high temperatures of 60 °C, and retains a capacity of 132.5 mAh g−1 after 300 cycles with a high capacity retention rate of 96.9%. Besides, PPI-CNT displays good electrochemical performance and compatibility in lithium-ion and potassium-ion batteries. This work provides an alternative optimization strategy for organic electrodes applied in long-lifetime metal ion batteries.